Metformin prevents ischemia reperfusion-induced oxidative stress in the fatty liver by attenuation of reactive oxygen species formation - Cahova, Monika; Palenickova, Eliska; Dankova, Helena; Sticova, Eva; Burian, Martin; Drahota, Zdenek; Cervinkova, Zuzana; Kucera, Otto; Gladkova, Christina; Stopka, Pavel; Krizova, Jana; Papackova, Zuzana; et al. (American journal of physiology: Gastrointestinal and liver physiology, 2015)
Nonalcoholic fatty liver disease is associated with chronic oxidative stress. In our study, we explored the antioxidant effect of antidiabetic metformin on chronic [high-fat diet (HFD)-induced] and acute oxidative stress induced by short-term warm partial ischemia-reperfusion (I/R) or on a combination of both in the liver. Wistar rats were fed a standard diet (SD) or HFD for 10 wk, half of them being administered metformin (150 mg·kg body wt −1 ·day −1 ). Metformin treatment prevented acute stress-induced necroinflammatory reaction, reduced alanine aminotransferase and aspartate aminotransferase serum activity, and diminished lipoperoxidation. The effect was more pronounced in the HFD than in the SD group. The metformin-treated groups exhibited less severe mitochondrial damage (markers: cytochrome c release, citrate synthase activity, mtDNA copy number, mitochondrial respiration) and apoptosis (caspase 9 and caspase 3 activation). Metformin-treated HFD-fed rats subjected to I/R exhibited increased antioxidant enzyme activity as well as attenuated mitochondrial respiratory capacity and ATP resynthesis. The exposure to I/R significantly increased NADH- and succinate-related reactive oxygen species (ROS) mitochondrial production in vitro. The effect of I/R was significantly alleviated by previous metformin treatment. Metformin downregulated the I/R-induced expression of proinflammatory (TNF-α, TLR4, IL-1β, Ccr2) and infiltrating monocyte (Ly6c) and macrophage (CD11b) markers. Our data indicate that metformin reduces mitochondrial performance but concomitantly protects the liver from I/R-induced injury. We propose that the beneficial effect of metformin action is based on a combination of three contributory mechanisms: increased antioxidant enzyme activity, lower mitochondrial ROS production, and reduction of postischemic inflammation.